Effect of Football on Fatigue of Patients with Breast Cancer Treated with Nano-Chemotherapy - Yu Zhang; Haonan Niu; Zhiwei Peng (Journal of Chemistry)
Cancer-related fatigue is one of the most common and uncontrollable subjective and persistent fatigue feelings in patients after breast cancer surgery, which seriously affects the rehabilitation effect and quality of life of patients. The purpose of this study was to investigate the effect of football intervention on cancer-related fatigue and quality of life in patients with breast cancer after nano-chemotherapy. The objective of this study is to explore the exercise program that can make patients actively carry out rehabilitation exercise and achieve good rehabilitation effect, so as to provide a theoretical and empirical basis for the study of cancer fatigue and quality of life of patients after breast cancer surgery. In this study, a quasi-experimental study method was used to conveniently select 60 breast cancer outpatients with tumor-related fatigue symptoms in a tertiary hospital in Liaoning Province. According to the convenience group, they were divided into a control group and an intervention group, 30 cases in each group. The control group received routine hospital nursing, while the intervention group received football intervention for 6 months on the basis of routine hospital nursing. The intervention measures include explaining the related knowledge of cancer-related fatigue, helping patients develop football projects, guiding patients to record football sports diaries, checking patients’ football sports diary records at the beginning of each chemotherapy cycle, and discussing football sports feelings with patients. After six months of intervention, the researchers assessed cancer-related fatigue symptoms and quality of life. Football can improve the fatigue, physiological, psychological, and psychological states of breast cancer patients after nano-chemotherapy; reduce fatigue, anxiety, and depression; improve sleep; and ultimately improve the quality of life.